Visible Light-Activated Carbon Dots for Inhibiting Biofilm Formation and Inactivating Biofilm-Associated Bacterial Cells - Dong, Xiuli; Overton, Christopher M.; Tang, Yongan; Darby, Jasmine P.; Sun, Ya-Ping; Yang, Liju (Frontiers in Bioengineering and Biotechnology, 2021)
This study was aimed to address the significant problems of bacterial biofilms found in medical fields and many industries. It explored the potential of a classical photoactive carbon dots (CDots), with 2,2′-(ethylenedioxy)bis(ethylamine) (EDA) for dot surface functionalization (thus EDA-CDots), for their inhibitory effect on B. subtilis biofilm formation and the inactivation of B. subtilis cells within established biofilm. The EDA-CDots were synthesized by chemical functionalization of selected small carbon nanoparticles with EDA molecules in amidation reactions. The inhibitory efficacy of CDots with visible light against biofilm formation was dependent significantly on the time point when CDots were added -- the earlier the CDots were added, the better inhibitory effect on the biofilm formation. The evaluation on antibacterial action of light-activated EDA-CDots against planktonic B. subtilis cells versus the cells in biofilm indicated that CDots were highly effective for inactivating planktonic cells, but barely inactivating cells in established biofilms. However, when coupling with chelating agents (e.g. EDTA) to target the biofilm architecture by breaking or weakening the EPS protection, much enhanced photoinactivation of biofilm-associated cells by CDots was achieved. The study demonstrated the potential of CDots to prevent the initiation of biofilm formation and to inhibit biofilm growth at early stage. Strategical combination treatment could enhance the effectiveness of photoinactivation by CDots to biofilm-associated cells.